Pengaruh Roe Dan Npm Terhadap Harga Saham Pada Bank BCA Tbk Periode 2013-2023 - Alya Zaharatul Hasanah; Apila Nabila Sari; Mutawali (CV. ITTC INDONESIA, 2025)
The purpose of this study is to determine the Return On Equity (ROE) and Net Profit Margin (NPM) on Stock Prices at Bank BCA Tbk in 2013-2023, both partially and simultaneously. The method used is a quantitative method. The sample used is the financial report of Bank BCA Tbk for 11 years. The sampling technique uses the Non Probability Sampling technique. The analysis of this study uses the SPSS (Staatistical Package For Social Science) software program version 29.0. The results of the study Return On Equity (ROE) does not have a significant effect on Stock Prices based on the results of the t-test (Partial Test) obtained a significant value (0.073> 0.05). Net Profit Margin (NPM) does not have a significant effect on Stock Prices obtained a significant value (0.183> 0.05). Return On Equity (ROE) and Net Profit Margin (NPM) do not affect Stock Prices. Based on the F test (Simultaneous Test) which shows that the significant value (0.093 > 0.05). The results of this study indicate that there is no simultaneous influence between Return On Equity (ROE) and Net Profit Margin (NPM) on Stock Prices at Bank BCA Tbk.